Lubricating-repairing bifunctional nano composite material as well as preparation method and application thereof

By incorporating repair agents and coated lubricants on nitrogen-doped multi-stage porous carbon nanorods, lubricated-repair dual-function nanocomposites are prepared, which solves the problems of lubrication failure and performance limitations of existing materials under high loads and special environments, and achieves high precision, high reliability and long-life anti-wear reduction and repair performance.

CN119552424APending Publication Date: 2025-03-04YANTAI ADVANCED MATERIALS & GREEN MFG SHANDONG PROVINCIAL LAB +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411794094.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing lubricating materials are prone to rupture of lubricating oil film under high loads, resulting in lubrication failure, and show performance limitations under special application scenarios such as oil-free, high and low temperatures, and radiation-proofing. At the same time, existing materials are difficult to take into account both wear-reduction and friction-reduction and repair performance, and cannot meet the requirements of high precision, high reliability and long life under harsh working conditions.

Method used

A nitrogen-doped multi-stage porous carbon nanorod is used as a matrix, with a built-in repair agent and a coating lubricant. Through vacuum impregnation and lubricant dispersion coating, a lubricating-repair bifunctional nanocomposite is prepared. This material uses multi-stage pore structure and carbon nanorods with high specific surface area to achieve effective storage and release of repair agents and lubricants, and improves the material's anti-wear, friction reduction and repair performance.

Benefits of technology

It achieves lubricating and repair performance with high accuracy, high reliability and long life under harsh working conditions, avoids the problem of lubricating oil film rupture, and shows excellent performance stability in special environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552424A_ABST
    Figure CN119552424A_ABST
Patent Text Reader

Abstract

The invention provides a lubricating-repairing bifunctional nano composite material as well as a preparation method and application thereof, and relates to the technical field of nano fillers. The invention provides a lubricating-repairing dual-function nano composite material. The lubricating-repairing dual-function nano composite material comprises a nitrogen-doped hierarchical pore carbon nanorod, a repairing agent and a lubricating agent, wherein the repairing agent is positioned in a pore channel of the nitrogen-doped hierarchical pore carbon nanorod, and the surface of the nitrogen-doped hierarchical pore carbon nanorod is coated with the lubricating agent. The nitrogen-doped hierarchical pore carbon nanorods are combined with the self-repairing agent and the lubricant, so that the nitrogen-doped hierarchical pore carbon nanorods have excellent friction-reducing, wear-resisting and repairing capabilities, can meet the application requirements in the fields of self-repairing and self-lubricating, and meet the requirements of high precision, high reliability and long service life of polymer-based self-lubricating materials under harsh working conditions; and the method has important significance for promoting the practical application of the polymer self-lubricating material in the modern high-end equipment industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano fillers, and in particular to a lubrication-repair dual-function nano composite material and a preparation method and application thereof. Background Art

[0002] The design and preparation of lubricating materials are key factors in achieving friction control and reliable lubrication. From the perspective of morphology, lubricating materials can be classified into solid lubricating materials, liquid lubricating materials and gas lubricating materials. Liquid lubricating materials are the largest and most widely used type of lubricating materials. During the friction process, they will form a fluid dynamic pressure or elastohydrodynamic lubrication pressure-bearing film on the friction contact surface to avoid direct contact between the rough peaks of the friction surface, thereby reducing friction and wear. However, liquid lubricating materials usually have low load-bearing capacity during use, and the lubricating oil film is prone to rupture under high loads, resulting in lubrication failure. In addition, in some special application scenarios such as oil-free, high and low temperature, radiation protection, etc., lubricating oils have serious performance limitations. In particular, under the influence of space radiation, they are prone to degradation and thickening, carbonization and degradation and drying, creep loss, and leakage pollution.

[0003] Wear is the inevitable result of friction, which directly leads to parts failure, poor performance of mechanical equipment, reduced efficiency and shortened service life. Using external repair agents or modifying mechanical materials to give them certain repair properties is an effective means to solve problems such as material wear and breakage. However, existing materials cannot take into account both anti-wear and friction reduction properties and repair properties, and it is difficult to meet the requirements of high precision, high reliability and long life for polymer-based self-lubricating materials under harsh working conditions. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a lubricating-repairing dual-function nanocomposite material and its preparation method and application, a self-lubricating-self-repairing polymer composite material and its application. The lubricating-repairing dual-function nanocomposite material provided by the present invention has excellent anti-wear and friction reduction performance and repair performance, and can meet the requirements of high precision, high reliability and long life for polymer-based self-lubricating materials under harsh working conditions.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The invention provides a lubrication-repair dual-function nanocomposite material, comprising nitrogen-doped multi-level porous carbon nanorods, a repair agent located in the pores of the nitrogen-doped multi-level porous carbon nanorods, and a lubricant coated on the surface of the nitrogen-doped multi-level porous carbon nanorods.

[0007] Preferably, the nitrogen-doped multi-level porous carbon nanorod has nanopores and mesopores, the mesopores have a pore size of 2 to 10 nm, and the nanopores have a pore size of 20 to 30 nm; the length of the nitrogen-doped multi-level porous carbon nanorod is 0.03 to 10 μm;

[0008] The mass content of the repair agent in the lubricating-repairing dual-function nanocomposite material is 20-62%, and the mass content of the lubricant is 5-20%;

[0009] The repair agent includes one or more of drying oil, isocyanate and epoxy resin;

[0010] The lubricant includes a solid lubricant.

[0011] The present invention also provides a method for preparing the lubricating-repairing dual-functional nanocomposite material described in the above technical solution, comprising the following steps:

[0012] The nitrogen-doped hierarchical porous carbon nanorods are mixed with a repairing agent and subjected to vacuum impregnation treatment to obtain hierarchical porous carbon nanorods containing the repairing agent;

[0013] The multi-level porous carbon nanorods containing the repairing agent are coated with a lubricant dispersion to obtain a lubricating-repairing dual-function nanocomposite material.

[0014] Preferably, the mass ratio of the nitrogen-doped hierarchical porous carbon nanorods to the repair agent is 5-10:1-5;

[0015] The nitrogen-doped hierarchical porous carbon nanorods are first subjected to vacuum treatment before use;

[0016] The vacuum degree of the vacuum impregnation treatment is -0.08 to -0.1 MPa, and the time is 2 to 4 hours.

[0017] Preferably, the lubricant dispersion is obtained by dispersing the lubricant in an organic solvent; the organic solvent includes one or more of ethanol, petroleum ether, isopropanol, carbon disulfide, xylene, ether, benzene, chloroform and carbon tetrachloride; the mass ratio of the lubricant to the organic solvent is 1:5-10;

[0018] The mass ratio of the lubricant to the multi-level porous carbon nanorods containing the repairing agent in the lubricant dispersion is 1:2-5.

[0019] Preferably, the method for preparing the nitrogen-doped hierarchically porous carbon nanorods comprises the following steps:

[0020] (1) self-assembling an ionic surfactant, a water-soluble polymer with opposite charges, and a non-ionic block copolymer under alkaline conditions to obtain a hierarchical pore structure template;

[0021] (2) Adding a silicon source and a carbon source into the hierarchical porous structure template, sequentially performing a hydrolysis and polycondensation reaction of the silicon source, deposition of the carbon source, carbonization and removal of silicon dioxide, to obtain doped hierarchical porous carbon nanorods.

[0022] Preferably, in step (1), the ionic surfactant comprises a long-chain alkyl quaternary ammonium salt or a Gemini quaternary ammonium salt surfactant;

[0023] The water-soluble high molecular polymer with opposite charges includes polyacrylic acid;

[0024] The nonionic block copolymer includes P123, L31 or L35;

[0025] The mass ratio of the ionic surfactant to the water-soluble high molecular polymer with opposite charges is 1:7-15;

[0026] The mass ratio of the ionic surfactant to the nonionic block copolymer is 1:4-16;

[0027] The self-assembly time is 30 to 60 minutes; the alkaline condition pH value is 8 to 10;

[0028] In step (2), the molar ratio of silicon in the silicon source to carbon in the carbon source is 1:5 to 20;

[0029] The temperature of the silicon source hydrolysis and polycondensation reaction is 25 to 80° C. and the time is 24 to 48 hours;

[0030] The temperature of the carbon source deposition is 25 to 80° C., and the time is 12 to 24 hours;

[0031] The carbonization includes pre-carbonization and high-temperature carbonization. The temperature of the pre-carbonization is 80-120° C. and the time is 24-48 hours; the temperature of the high-temperature carbonization is 800-900° C. and the time is 4-6 hours.

[0032] The present invention also provides the use of the lubricating-repairing dual-functional nanocomposite material described in the above technical solution or the lubricating-repairing dual-functional nanocomposite material prepared by the preparation method described in the above technical solution as a filler.

[0033] The present invention also provides a self-lubricating-self-repairing polymer composite material comprising a polymer and a filler, wherein the filler comprises the lubricating-repairing dual-functional nanocomposite material described in the above technical solution or the lubricating-repairing dual-functional nanocomposite material prepared by the preparation method described in the above technical solution.

[0034] The present invention also provides the use of the self-lubricating-self-repairing polymer composite material described in the above technical solution in mechanical parts in the fields of petrochemical industry, aerospace, automobile industry or marine heavy industry.

[0035] The present invention provides a lubrication-repair dual-function nanocomposite material, comprising nitrogen-doped multi-level porous carbon nanorods, a repair agent located in the pores of the nitrogen-doped multi-level porous carbon nanorods, and a lubricant coated on the surface of the nitrogen-doped multi-level porous carbon nanorods. The nitrogen-doped multi-level porous carbon nanorods have the advantages of a wide range of carbon sources, low cost, large specific surface area and pore volume, and are easy to carry out surface chemical modification treatment, which has significant advantages in improving the interface compatibility of the material with the self-repairing agent and the lubricant.

[0036] The compounding of lubricants or repair agents with porous materials belongs to solid-liquid compounding, and the leakage of lubricants / repair agents in porous materials and other problems need to be considered, and it is difficult to coordinate the compatibility between two or more additives and porous materials and storage and other problems. The present invention uses nitrogen-doped multi-level porous carbon nanorods as medium storage units, fully utilizing the advantages of the rich multi-level pore structure, high specific surface area and pore volume of the multi-level porous carbon nanorods, and simultaneously carrying the repair agent and lubricant to achieve a multifunctional design of a single modified material, avoiding problems such as poor compatibility between multiple components, and is of great significance for greatly improving the friction reduction and anti-wear performance of nano-composite materials and the service life of the materials, and broadening their application in aerospace, marine engineering and other fields.

[0037] The dual-function multi-level porous carbon nanorods provided by the present invention have excellent anti-friction and anti-wear and repair capabilities. On the one hand, during the friction process, the friction heat generated by the shearing action of the friction pair causes the lubricant coated on the outside of the nitrogen-doped multi-level porous carbon nanorods to change from a solid state to a molten state, and is gradually released to the surface of the friction pair to form a lubricating oil film with good lubrication performance; on the other hand, the nitrogen-doped multi-level porous carbon nanorods serve as a storage medium unit of the repair agent. During the friction process, due to the compression action of the friction pair, the repair agent stored in the nitrogen-doped multi-level porous carbon nanorods is released into the wear area of ​​the friction pair, gradually forming a repair layer to efficiently repair the wear area. The lubrication-repair dual-function nanocomposite material provided by the present invention has excellent anti-friction and anti-friction performance and repair performance, can meet the application requirements in the field of self-repair and self-lubrication, and meet the requirements of high precision, high reliability and long life for polymer-based self-lubricating materials under harsh working conditions, which is of great significance for promoting the practical application of polymer self-lubricating materials in the modern high-end equipment industry.

[0038] The present invention adopts a vacuum impregnation method to load a repair agent on nitrogen-doped multi-level porous carbon nanorods, and uses the oxidation of the repair agent to form a self-healing film to play a self-repairing role; the lubricant dispersion solution is coated on the lubrication-repair dual-function nanocomposite material, and the lubricant can not only be used as a part of the wall material to encapsulate the pore structure of the nitrogen-doped multi-level porous carbon nanorods, but also can be used as a good lubricant to improve the tribological properties of the composite material. The preparation method provided by the present invention is simple, effective, green and environmentally friendly, and the prepared lubrication-repair dual-function nanocomposite material has both excellent repair and lubrication functions.

[0039] The present invention also provides a self-lubricating-self-repairing polymer composite material including a polymer and a filler, wherein the filler includes the lubricating-repairing dual-function nanocomposite material described in the above technical solution or the lubricating-repairing dual-function nanocomposite material prepared by the preparation method described in the above technical solution. The present invention adds a lubricating-repairing dual-function nanocomposite material combining nitrogen-doped multi-level porous carbon nanorods, a repairing agent and a lubricant to the polymer, and the rich nanopore structure in the carbon nanorods provides sufficient storage space for the repairing agent, which can act as a buffer pool for the repairing agent under instantaneous high temperature and high pressure to achieve continuous sustained release of the repairing agent, while the mesoporous and microporous structures can store a large amount of repairing agents, and the interconnected pore structure is conducive to the efficient transmission and diffusion of the repairing agent, and quickly forms a high-quality repair film on the surface of the friction pair. Under the action of friction heat, the coated lubricant will be converted from solid to liquid, forming a lubricating oil film on the surface of the friction pair. Under the synergistic effect of the lubricant and the repairing agent, the purpose of improving the wear-reducing and anti-wear performance of the composite material and repairing the damaged composite material is achieved, and the maintenance cost is reduced to achieve repeated use of the composite material and extend the service life of the composite material. The self-lubricating-self-repairing polymer composite material provided by the present invention has good application prospects in mechanical parts in the fields of petrochemical industry, aerospace, automobile industry or marine heavy industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 TEM image (a) and high-magnification TEM image (b) of the nitrogen-doped hierarchical porous carbon nanorods prepared in Example 1;

[0041] Figure 2 The nitrogen adsorption-desorption isotherm (a) and the corresponding pore size distribution curve (b) of the lubrication-repair dual-functional nanocomposite prepared in Example 1;

[0042] Figure 3 The SEM images of the lubrication-repair dual-functional nanocomposite prepared in Example 1 at different magnifications;

[0043] Figure 4 Thermogravimetric curves of the nitrogen-doped hierarchical porous carbon nanorods, the hierarchical porous carbon nanorods containing a repairing agent, and the lubricating-repairing dual-functional nanocomposite material prepared in Example 1;

[0044] Figure 5 The scanning electron microscope image (a) of the surface of the self-lubricating-self-healing polymer composite material prepared in Example 2 and the surface roughness of the sample (b);

[0045] Figure 6 The SEM images of the cross-section of the self-lubricating and self-repairing polymer composite material prepared in Example 3 at different magnifications;

[0046] Figure 7 The hardness test results of the pure epoxy resin sample and the self-lubricating-self-repairing polymer composite material prepared in Example 1 and Comparative Example 1 are shown;

[0047] Figure 8 Curves showing the change of friction coefficient over time of the self-lubricating-self-repairing polymer composite material prepared by pure epoxy resin, Example 1 and Comparative Example 1 under test condition 1;

[0048] Fig. 9 This is a curve showing the change of the friction coefficient over time of the self-lubricating and self-repairing polymer composite material prepared in Example 2 under test condition 2;

[0049] Fig.10 The friction coefficient variation curve of the self-lubricating-self-repairing polymer composite material and pure epoxy resin prepared in Example 3 under test condition 1 over time;

[0050] Fig.11 The friction coefficient variation curve of the self-lubricating-self-repairing polymer composite material and pure epoxy resin prepared in Example 4 under test condition 1 over time;

[0051] Fig.12 This is a curve showing the change of the friction coefficient over time of the self-lubricating and self-repairing polymer composite material prepared in Comparative Example 2 under test condition 1;

[0052] Fig.13 The curve of the friction coefficient of the self-lubricating-self-repairing polymer composite material prepared in Example 5 under test condition 2 is a curve of the friction coefficient changing with time;

[0053] Fig.14 The ultra-depth-of-field microscopy images (a and c) of the self-lubricating-self-healing polymer composite material (c and d) and pure epoxy resin (a and b) prepared in Example 4 at the wear scar after the friction test and the ultra-depth-of-field microscopy images (b and d) after self-healing;

[0054] Fig.15 The depth variation curve of the wear scar before and after repair of the self-lubricating and self-repairing polymer composite material prepared in Example 4 and pure epoxy resin. DETAILED DESCRIPTION

[0055] The invention provides a lubrication-repair dual-function nanocomposite material, comprising nitrogen-doped multi-level porous carbon nanorods, a repair agent located in the pores of the nitrogen-doped multi-level porous carbon nanorods, and a lubricant coated on the surface of the nitrogen-doped multi-level porous carbon nanorods.

[0056] In the present invention, the nitrogen-doped multi-level porous carbon nanorods preferably have nanopores and mesopores, the pore size of the mesopores is preferably 2-10 nm, and in specific embodiments, it can be 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm or 10nm; the pore size of the nanopores is preferably 20-30 nm, and in specific embodiments, it can be 20nm, 21nm, 22nm, 23nm, 24nm, 25nm, 26nm, 27nm, 28nm, 29nm or 30nm; the length of the nitrogen-doped multi-level porous carbon nanorods is preferably 0.03-10 μm, and in specific embodiments, it can be 0.03 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm. The nitrogen-doped multi-level porous carbon nanorods used in the present invention have a multi-level pore structure, and its rich pore structure is conducive to the storage and mass transfer diffusion of lubricants and repair agents in the material; the multi-level pore structure can also increase its specific surface area, which is conducive to surface chemical modification and improves the compatibility of the material with the lubricant and the polymer matrix; the rod-like morphology can play the role of a micro-bearing in the friction process, and can change sliding friction into rolling friction, effectively reducing the friction coefficient, which can not only significantly improve the anti-wear and friction-reducing properties of the lubricant, but also especially increase the limit load of the lubricant operation and improve the working conditions in harsh environments.

[0057] In the present invention, the repair agent includes one or more of drying oil, isocyanate and epoxy resin; the drying oil preferably includes vegetable oil, and in a specific embodiment, it can be linseed oil and / or tung oil. In the present invention, the mass content of the repair agent in the lubricating-repairing dual-function nanocomposite material is preferably 20-62%, and in a specific embodiment, it can be 20%, 25%, 30%, 35%, 40%, 42%, 45%, 50%, 55%, 60% or 62%.

[0058] In the present invention, the lubricant preferably includes a solid lubricant, more preferably a solid lubricant that softens and melts during use, and in a specific embodiment, it can be one or both of coconut oil and paraffin. In the present invention, the mass content of the lubricant in the lubrication-repair dual-function nanocomposite material is 5-20%, and in a specific embodiment, it can be 5%, 8%, 10%, 12%, 15%, 17% or 20%.

[0059] The compounding of lubricants or repair agents with porous materials belongs to solid-liquid compounding, and it is necessary to consider the leakage of lubricants / repair agents in porous materials, and it is difficult to coordinate the compatibility between two or more additives and porous materials, as well as storage and other issues. The present invention uses nitrogen-doped multi-level porous carbon nanorods as medium storage units, making full use of the advantages of the rich multi-level pore structure, high specific surface area and pore volume of multi-level porous carbon nanorods, while carrying repair agents and lubricants, realizing the multifunctional design of a single modified material, and avoiding problems such as poor compatibility between multiple components. It is of great significance to greatly improve the anti-friction and anti-wear properties of nano-composite materials and the service life of materials, and broaden their application in aerospace, marine engineering and other fields.

[0060] The compounding of lubricants or repair agents with porous materials belongs to solid-liquid compounding, and the leakage of lubricants / repair agents in porous materials and other problems need to be considered, and it is difficult to coordinate the compatibility between two or more additives and porous materials and storage and other problems. The present invention uses nitrogen-doped multi-level porous carbon nanorods as medium storage units, fully utilizing the advantages of the rich multi-level pore structure, high specific surface area and pore volume of the multi-level porous carbon nanorods, and simultaneously carrying the repair agent and lubricant to achieve a multifunctional design of a single modified material, avoiding problems such as poor compatibility between multiple components, and is of great significance for greatly improving the friction reduction and anti-wear performance of nano-composite materials and the service life of the materials, and broadening their application in aerospace, marine engineering and other fields.

[0061] The lubrication-repair dual-function nanocomposite material provided by the present invention has excellent anti-wear and friction reduction properties and repair properties, and can meet the requirements of high precision, high reliability and long life for polymer-based self-lubricating materials under harsh working conditions. It is of great significance to promote the practical application of polymer self-lubricating materials in the modern high-end equipment industry.

[0062] The present invention also provides a method for preparing the lubricating-repairing dual-functional nanocomposite material described in the above technical solution, comprising the following steps:

[0063] The nitrogen-doped hierarchical porous carbon nanorods are mixed with a repairing agent and subjected to vacuum impregnation treatment to obtain hierarchical porous carbon nanorods containing the repairing agent;

[0064] The multi-level porous carbon nanorods containing the repairing agent are coated with a lubricant dispersion to obtain a lubricating-repairing dual-function nanocomposite material.

[0065] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0066] The invention mixes nitrogen-doped multi-level porous carbon nanorods with a repairing agent, and performs vacuum impregnation treatment to obtain the multi-level porous carbon nanorods containing the repairing agent.

[0067] In the present invention, the mass ratio of the nitrogen-doped hierarchical porous carbon nanorods to the repairing agent is preferably 5-10:1-5, and in specific embodiments can be 5:1, 5:2, 5:3, 5:4, 5:5, 6:1, 6:2, 6:3, 6:4, 6:5, 7:1, 7:2, 7:3, 7:4, 7:5, 8:1, 8:2, 8:3, 8:5, 9:1, 9:2, 9:4, 9:5, 10:1, 10:2 or 10:3. In the present invention, the repairing agent is preferably used in the form of a repairing agent dispersion, and the organic solvent in the repairing agent dispersion preferably includes ethanol and / or petroleum ether. In the present invention, the mass ratio of the repair agent to the organic solvent is preferably 1:5-10, and in specific embodiments, it can be 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5 or 1:10. In the present invention, the repair agent dispersion is preferably obtained by dispersing the repair agent in an organic solvent; the dispersion preferably includes ultrasonic dispersion, and the power of the ultrasonic dispersion is preferably 100-300W, and in specific embodiments, it can be 100W, 150W, 200W, 250W or 300W; the time of the ultrasonic dispersion is preferably 30-60min, and in specific embodiments, it can be 30min, 40min, 50min or 60min.

[0068] In the present invention, the nitrogen-doped multi-level porous carbon nanorods are preferably subjected to a vacuum treatment before use; the temperature of the vacuum treatment is preferably 25 to 30°C, and in specific embodiments, it can be 25°C, 26°C, 27°C, 28°C, 29°C or 30°C; the vacuum degree of the vacuum treatment is preferably -0.08 to -0.1MPa, and in specific embodiments, it can be -0.08MPa, -0.09MPa or -0.1MPa; the time of the vacuum treatment is preferably 60 to 120min, and in specific embodiments, it can be 60min, 70min, 80min, 90min, 100min, 110min or 120min. In the present invention, the purpose of the vacuum treatment is to remove the gas adsorbed in the nitrogen-doped multi-level porous carbon nanorods.

[0069] In the present invention, the repair agent is preferably added under vacuum conditions; the vacuum degree of the vacuum conditions is preferably -0.08 to -0.1 MPa, and in specific embodiments may be -0.08 MPa, -0.09 MPa or -0.1 MPa.

[0070] In the present invention, the vacuum degree of the vacuum impregnation treatment is preferably -0.08 to -0.1 MPa, and in specific embodiments it can be -0.08 MPa, -0.09 MPa or -0.1 MPa; the time of the vacuum impregnation treatment is preferably 2 to 4 hours, and in specific embodiments it can be 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0071] After completing the vacuum impregnation treatment, the present invention preferably further comprises: distilling and drying the impregnation system obtained by the vacuum impregnation treatment to obtain a multi-level porous carbon nanorod containing a repairing agent. In the present invention, the drying temperature is preferably 40 to 60°C, and in a specific embodiment it can be 40°C, 45°C, 50°C, 55°C or 60°C; the present invention has no special limitation on the drying time, and it can be dried to constant weight.

[0072] In the present invention, the method for preparing the nitrogen-doped hierarchically porous carbon nanorods preferably comprises the following steps:

[0073] (1) self-assembling an ionic surfactant, a water-soluble polymer with opposite charges, and a non-ionic block copolymer under alkaline conditions to obtain a hierarchical pore structure template;

[0074] (2) Adding a silicon source and a carbon source into the hierarchical porous structure template, sequentially performing a hydrolysis and polycondensation reaction of the silicon source, deposition of the carbon source, carbonization and removal of silicon dioxide, to obtain doped hierarchical porous carbon nanorods.

[0075] The invention self-assembles an ionic surfactant, a water-soluble high molecular polymer with opposite charges and a non-ionic block copolymer under alkaline conditions to obtain a multi-level pore structure template.

[0076] In the present invention, the ionic surfactant preferably includes a long-chain alkyl quaternary ammonium salt or a Gemini quaternary ammonium salt surfactant, and more preferably includes one of cetyltrimethylammonium bromide (CTAB), octadecyltrimethylammonium chloride, cetyldimethylethylenediamine salt, tetradecylammonium chloride and cetylpyridinium chloride monohydrate.

[0077] In the present invention, the oppositely charged water-soluble polymer preferably includes polyacrylic acid; the oppositely charged water-soluble polymer is preferably used in the form of an oppositely charged water-soluble polymer aqueous solution, and the concentration of the oppositely charged water-soluble polymer aqueous solution is preferably 10 to 35wt%, and in specific embodiments it can be 10wt%, 15wt%, 20wt%, 25wt%, 30wt% or 35wt%.

[0078] In the present invention, the mass ratio of the ionic surfactant to the oppositely charged water-soluble high molecular polymer is preferably 1:7-15, and in specific embodiments may be 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14 or 1:15.

[0079] In the present invention, the nonionic block copolymer preferably includes P123, L31 or L35; the nonionic block copolymer is preferably used in the form of a nonionic block copolymer aqueous solution, and the concentration of the nonionic block copolymer aqueous solution is preferably 3-10wt%, and in specific embodiments it can be 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%.

[0080] In the present invention, the mass ratio of the ionic surfactant to the nonionic block copolymer is preferably 1:4-16, and in specific embodiments it can be 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15 or 1:16.

[0081] In the present invention, the pH value of the alkaline condition is preferably 8 to 10, and in a specific embodiment, it can be 8, 8.5, 9, 9.5 or 10. In the present invention, the alkaline reagent used in the alkaline condition preferably includes ammonia water and / or an organic amine; the concentration of the ammonia water is preferably 25 to 28 wt%, and in a specific embodiment, it can be 25 wt%, 26 wt%, 27 wt% or 28 wt%; the organic amine preferably includes dimethylamine and / or triethylamine.

[0082] In the present invention, the self-assembly preferably comprises: stirring and mixing an ionic surfactant, a water-soluble polymer with opposite charges, an aqueous solution of a non-ionic block copolymer and a solvent, and adding an alkaline reagent under stirring conditions for self-assembly. In the present invention, the solvent preferably comprises water, and the ratio of the mass of the ionic surfactant to the volume of the solvent is preferably 1g:25-55mL, and in specific embodiments can be 1g:25mL, 1g:30mL, 1g:35mL, 1g:40mL, 1g:45mL, 1g:50mL or 1g:55mL.

[0083] In the present invention, the temperature of the self-assembly is preferably room temperature; the time of the self-assembly is 30 to 60 minutes, and in specific embodiments it can be 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes.

[0084] After obtaining the multi-level porous structure template, the present invention adds silicon source and carbon source into the multi-level porous structure template, sequentially performs silicon source hydrolysis and polycondensation reaction, carbon source deposition, carbonization and silicon dioxide removal to obtain doped multi-level porous carbon nanorods.

[0085] In the present invention, the silicon source preferably includes one or more of methyl orthosilicate, ethyl orthosilicate and trimethoxysilane. In the present invention, the carbon source preferably includes one or more of sucrose, fructose, dopamine, xylose, lignin and arabinose. In the present invention, the molar ratio of silicon in the silicon source to carbon in the carbon source is preferably 1:5 to 20, and in specific embodiments it can be 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20.

[0086] In the present invention, the temperature of the silicon source hydrolysis and polycondensation reaction is preferably 25-80°C, and in specific embodiments it can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C; the time of the silicon source hydrolysis and polycondensation reaction is preferably 24-48h, and in specific embodiments it can be 24h, 25h, 26h, 27h, 28h, 29h, 30h, 31h, 32h, 33h, 34h, 35h, 36h, 37h, 38h, 39h, 40h, 41h, 42h, 43h, 44h, 45h, 46h, 47h or 48h.

[0087] In the present invention, the temperature of the carbon source deposition is preferably 25-80°C, and in specific embodiments it can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C; the time of the carbon source deposition is preferably 12-24h, and in specific embodiments it can be 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h or 24h.

[0088] In the present invention, the carbonization preferably includes pre-carbonization and high-temperature carbonization. In the present invention, the pre-carbonization temperature is preferably 80-120°C, and in specific embodiments, it can be 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 105°C or 120°C; the pre-carbonization time is preferably 24-48h, and in specific embodiments, it can be 24h, 25h, 26h, 27h, 28h, 29h, 30h, 31h, 32h, 33h, 34h, 35h, 36h, 37h, 38h, 39h, 40h, 41h, 42h, 43h, 44h, 45h, 46h, 47h or 48h.

[0089] After completing the pre-carbonization, the present invention preferably further comprises: performing solid-liquid separation on the product obtained by the pre-carbonization, washing the obtained solid product with water and then drying it, and then performing high-temperature carbonization. In the present invention, the solid-liquid separation preferably comprises centrifugal separation. In the present invention, the drying temperature is preferably 60 to 80°C, and in specific embodiments it can be 60°C, 65°C, 70°C, 75°C or 80°C; the present invention has no special limitation on the drying time, and it can be dried to constant weight.

[0090] In the present invention, the temperature of the high-temperature carbonization is preferably 800-900°C, and in specific embodiments it can be 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C or 900°C; the time of the high-temperature carbonization is preferably 4-6h, and in specific embodiments it can be 4h, 4.5h, 5h, 5.5h or 6h; the high-temperature carbonization is preferably carried out under a protective atmosphere, and the protective atmosphere preferably includes nitrogen, argon or helium.

[0091] In the present invention, the silicon dioxide removal preferably includes etching, and the etching agent for etching preferably includes a strong acid or a strong base; the strong acid preferably includes HF; the strong base preferably includes an alkali metal hydroxide, and more preferably includes sodium hydroxide and / or potassium hydroxide. In the present invention, the etching agent is preferably used in the form of an etching agent aqueous solution, and the mass concentration of the etching agent aqueous solution is preferably 1-10wt%, and in specific embodiments, it can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%. In the present invention, the mass ratio of the etching agent (excluding water) to the carbonized product is preferably ≥4, more preferably 4-10, and in specific embodiments, it can be 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5 or 10.

[0092] In the present invention, the etching temperature is preferably room temperature, and the etching time is preferably 12 to 24 hours, and in specific embodiments it can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours.

[0093] After the etching is completed, the present invention preferably further comprises: washing the product obtained by the etching with water and then drying to obtain doped multi-level porous carbon nanorods. In the present invention, the drying temperature is preferably 60 to 80°C, and in specific embodiments it can be 60°C, 65°C, 70°C, 75°C or 80°C; the present invention has no special limitation on the drying time, and it can be dried to constant weight.

[0094] After obtaining the multi-level porous carbon nanorods containing the repairing agent, the present invention uses a lubricant dispersion to coat the multi-level porous carbon nanorods containing the repairing agent to obtain a lubricating-repairing dual-functional nanocomposite material.

[0095] In the present invention, the lubricant dispersion is preferably obtained by dispersing the lubricant in an organic solvent; the organic solvent includes one or more of ethanol, petroleum ether, isopropanol, carbon disulfide, xylene, ether, benzene, chloroform and carbon tetrachloride; the mass ratio of the lubricant to the organic solvent is 1:5-10, and in specific embodiments, it can be 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5 or 1:10. In the present invention, the dispersion preferably includes ultrasonic dispersion, and the power of the ultrasonic dispersion is preferably 100-300W, and in specific embodiments, it can be 100W, 150W, 200W, 250W or 300W; the time of the ultrasonic dispersion is preferably 30-60min, and in specific embodiments, it can be 30min, 40min, 50min or 60min.

[0096] In the present invention, the mass ratio of the lubricant to the hierarchical porous carbon nanorods containing the repair agent in the lubricant dispersion is preferably 1:2-5, and in specific embodiments it can be 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5 or 1:5.

[0097] In the present invention, the coating treatment preferably includes spraying. Specifically, the multi-level porous carbon nanorods containing the repairing agent are spread on the substrate and the lubricant dispersion is sprayed. In the present invention, the material of the substrate preferably includes one or more of glass, polytetrafluoroethylene and polymethyl methacrylate board. In the present invention, the number of spraying is preferably 2 to 3 times to ensure that the lubricant completely covers the multi-level porous carbon nanorods containing the repairing agent; after each spraying, the mixture is collected and mixed evenly by a high-speed homogenizer; the speed of the high-speed homogenizer is preferably 1500 to 3000 r / min, and in specific embodiments it can be 1500 r / min, 2000 r / min or 2500 r / min, 3000 r / min.

[0098] The present invention adopts a vacuum impregnation method to load a repair agent on nitrogen-doped multi-level porous carbon nanorods, and uses the oxidation of the repair agent to form a self-healing film to play a self-repairing role; the lubricant dispersion solution is coated on the lubrication-repair dual-function nanocomposite material, and the lubricant can not only be used as a part of the wall material to encapsulate the pore structure of the nitrogen-doped multi-level porous carbon nanorods, but also can be used as a good lubricant to improve the tribological properties of the composite material. The preparation method provided by the present invention is simple, effective, green and environmentally friendly, and the prepared lubrication-repair dual-function nanocomposite material has both excellent repair and lubrication functions.

[0099] The present invention combines bifunctional multi-level porous carbon nanorods with a self-healing agent and a lubricant to prepare a nanocomposite material with the dual functions of self-lubrication and self-repairing, thereby achieving simultaneous improvement of the friction reduction and anti-wear effects of the nanocomposite material and the function of repairing damaged composite materials. The preparation method is simple, effective and environmentally friendly.

[0100] The present invention also provides the use of the lubricating-repairing dual-functional nanocomposite material described in the above technical solution or the lubricating-repairing dual-functional nanocomposite material prepared by the preparation method described in the above technical solution as a filler.

[0101] The dual-function multi-level porous carbon nanorods provided by the present invention have excellent anti-friction and anti-wear and repair capabilities. On the one hand, during the friction process, the friction heat generated by the shearing action of the friction pair causes the lubricant coated on the outside of the nitrogen-doped multi-level porous carbon nanorods to change from a solid state to a molten state, and is gradually released to the surface of the friction pair to form a lubricating oil film with good lubrication performance; on the other hand, the nitrogen-doped multi-level porous carbon nanorods serve as a storage medium unit for the repair agent. During the friction process, due to the compression action of the friction pair, the repair agent stored in the nitrogen-doped multi-level porous carbon nanorods is released into the wear area of ​​the friction pair, gradually forming a repair layer to efficiently repair the wear area. The lubrication-repair dual-function nanocomposite material provided by the present invention has excellent anti-friction and anti-wear properties and repair properties. As a filler, it can meet the application requirements in the field of self-repair and self-lubrication, and meet the requirements of high precision, high reliability and long life for polymer-based self-lubricating materials under harsh working conditions. It is of great significance to promote the practical application of polymer self-lubricating materials in the modern high-end equipment industry.

[0102] The present invention also provides a self-lubricating-self-repairing polymer composite material including a polymer and a filler, wherein the filler includes the lubricating-repairing dual-functional nanocomposite material described in the above technical solution or the lubricating-repairing dual-functional nanocomposite material prepared by the preparation method described in the above technical solution. In the present invention, the polymer preferably includes one or more of epoxy resin, polyester resin, vinyl ester, bismaleimide, polyamide resin and thermosetting polyimide. In the present invention, the mass of the filler in the self-lubricating-self-repairing polymer composite material accounts for 3 to 35% of the mass of the polymer, and in specific embodiments it can be 3%, 5%, 10%, 15%, 20%, 25%, 30% or 35%.

[0103] The present invention adds a lubricating-repairing dual-function nanocomposite material combining nitrogen-doped multi-level porous carbon nanorods, a repairing agent and a lubricant to a polymer. The rich nanopore structure in the carbon nanorods provides sufficient storage space for the repairing agent, and can act as a buffer pool for the repairing agent under instantaneous high temperature and high pressure to achieve continuous sustained release of the repairing agent. The mesoporous and microporous structures can store a large amount of repairing agents, and the interconnected pore structure is conducive to the efficient transmission and diffusion of the repairing agent, and quickly forms a high-quality repair film on the surface of the friction pair. Under the action of friction heat, the coated lubricant will be converted from solid to liquid, forming a lubricating oil film on the surface of the friction pair. Under the synergistic effect of the lubricant and the repairing agent, the purpose of improving the wear-reducing and anti-wear performance of the composite material and repairing the damaged composite material is achieved, and the maintenance cost is reduced to achieve repeated use of the composite material and extend the service life of the composite material.

[0104] In the present invention, the method for preparing the self-lubricating and self-repairing polymer composite material preferably comprises the following steps: blending a polymer with a filler, adding a curing agent for curing, and obtaining the self-lubricating and self-repairing polymer composite material.

[0105] In the present invention, the mass ratio of the filler to the polymer is preferably 0.03-0.35:1, and in specific embodiments may be 0.03:1, 0.04:1, 0.05:1, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1 or 0.35:1.

[0106] In the present invention, the blending temperature is preferably 30-45°C, and in specific embodiments it can be 30°C, 35°C, 40°C or 45°C; the blending time is preferably 30-60min, and in specific embodiments it can be 30min, 40min, 50min or 60min; the blending is preferably carried out under stirring conditions.

[0107] After completing the blending, the present invention preferably further comprises: vacuum degassing the suspension obtained by the blending, and the vacuum degassing is preferably carried out under stirring conditions; the vacuum degree of the vacuum degassing is preferably -98 to -101 kPa, and in specific embodiments it can be -98 kPa, -99 kPa, -100 kPa or -101 kPa.

[0108] In the present invention, the curing agent preferably includes triethylenetetramine and / or diethylenetriamine. In the present invention, the mass ratio of the curing agent to the polymer is preferably 0.1 to 0.3:1, and in specific embodiments can be 0.1:1, 0.15:1, 0.2:1, 0.25:1 or 0.3:1.

[0109] In the present invention, it is preferred to add a curing agent, stir and deaerate, and then perform curing. In the present invention, the stirring temperature is preferably room temperature; the stirring time is preferably 5 to 10 minutes, and in a specific embodiment, it can be 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes or 10 minutes. In the present invention, the deaeration is preferably performed in a homogenizer.

[0110] In the present invention, the curing preferably includes performing a first curing and a second curing in sequence; the temperature of the first curing is preferably room temperature, and the time of the first curing is preferably 2 to 8 hours, and in a specific embodiment, it can be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours; the temperature of the second curing is preferably 80 to 150°C, and in a specific embodiment, it can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C; the time of the second curing is preferably 8 to 24 hours, and in a specific embodiment, it can be 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours.

[0111] The present invention also provides the application of the self-lubricating-self-repairing polymer composite material described in the above technical solution in mechanical parts in the fields of petrochemical, aerospace, automobile industry or marine heavy industry. In the present invention, the mechanical parts preferably include gears, bearings, pistons, seals or guide wheels. The present invention adds a lubricating-repairing dual-function nanocomposite material combining nitrogen-doped multi-level porous carbon nanorods and a repair agent and a lubricant to a polymer. The rich nanopore structure in the carbon nanorod provides sufficient storage space for the repair agent, which can act as a buffer pool for the repair agent under instantaneous high temperature and high pressure to achieve continuous sustained release of the repair agent, while the mesoporous and microporous structures can store a large amount of repair agents, and the interconnected pore structure is conducive to the efficient transmission and diffusion of the repair agent, and quickly forms a high-quality repair film on the surface of the friction pair. Under the action of friction heat, the coated lubricant will be converted from solid to liquid, forming a lubricating oil film on the surface of the friction pair. Under the synergistic effect of the lubricant and the repair agent, the purpose of improving the wear-reducing and anti-wear performance of the composite material and repairing the damaged composite material is achieved, and the maintenance cost is reduced to achieve repeated use of the composite material and extend the service life of the composite material. The self-lubricating-self-repairing polymer composite material provided by the present invention has good application prospects in mechanical parts in the fields of petrochemical industry, aerospace, automobile industry or marine heavy industry.

[0112] In order to further illustrate the present invention, the lubrication-repair dual-function nanocomposite material and its preparation method and application, the self-lubrication-self-repairing polymer composite material and its application provided by the present invention are described in detail below in combination with the embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0113] Example 1

[0114] At room temperature, 0.55g hexadecyltrimethylammonium bromide (CTAB), 3.0g polyacrylic acid aqueous solution (25wt%, PAA) and 4.0g 5wt% P123 aqueous solution were dissolved in 30mL molecular water, and the mixed solution was rapidly stirred at 500r / min for 30min, and then 5.2g ammonia aqueous solution (28wt%) was added under stirring, and 2.08g TEOS was added. After stirring for 5min, 4.28g sucrose (C / Si molar ratio was 15) was added. The time interval between the addition of the two systems was 5min, and the stirring was continued for 30min at room temperature. After the stirring was completed, the reaction system was transferred to a reactor and placed in an oven at 80℃ for 48h. The reaction product was centrifuged and washed with deionized water twice, and dried at 70℃ to constant weight to obtain a dark brown powder. The obtained dark brown powder was carbonized at 900°C for 6 h under a nitrogen atmosphere, and the silica was removed by an excess (HF to high-temperature carbonization product mass ratio of 6) 10 wt% HF aqueous solution. The powder was washed with deionized water and dried at 70°C in a vacuum oven to constant weight to obtain nitrogen-doped hierarchical porous carbon nanorods (denoted as NPCS).

[0115] 5 g of linseed oil and 20 g of anhydrous ethanol were mixed to obtain a linseed oil ethanol dispersion; 5 g of nitrogen-doped hierarchical porous carbon nanorods were subjected to vacuum treatment (4 h) to remove the gas adsorbed in the pores, and then mixed with the above linseed oil ethanol dispersion under vacuum (-0.1 MPa) and immersed for 4 h, and the above mixture was subjected to rotary evaporation for 4 h to remove the ethanol in the mixture, and the obtained oil-carrying powder was dried in a vacuum oven at 60° C. for 12 h to obtain hierarchical porous carbon nanorods containing a repairing agent (denoted as NPCS-LO, wherein the mass content of linseed oil is 50%);

[0116] 1 g of solid paraffin was dissolved in 2 g of petroleum ether to obtain a petroleum ether dispersion of paraffin, which was placed in a spray gun for later use. The above 5 g of NPCS-LO was evenly spread on a glass plate, and the NPCS-LO-1 was coated with paraffin by spraying with a spray gun. The dispersion was placed in a vacuum oven at 30°C and dried for 12 h to obtain a lubricating-repairing dual-functional nanocomposite material (denoted as NPCS-LO@WAX, wherein the mass content of paraffin was 10%).

[0117] 3g NPCS-LO@WAX and 10g epoxy resin were stirred and blended, and stirred continuously for 1h in a 45℃ water bath to obtain a suspension, which was evenly dispersed under vacuum degassing (-98kPa) and stirring. Then, 1.5g triethylenetetramine curing agent was added to the suspension and stirred for 5min. The above solution was placed in a homogenizer for degassing and poured into a polytetrafluoroethylene mold. It was first cured at room temperature for 2h, and then cured at 80℃ for 12h to obtain a self-lubricating-self-healing polymer composite material.

[0118] Figure 1 TEM image (a) and high-magnification TEM image (b) of the nitrogen-doped hierarchical porous carbon nanorods prepared in Example 1. Figure 1 It can be seen that the nitrogen-doped hierarchical porous carbon nanorods have good dispersion, the particles show a regular rod-like morphology, the diameter of the carbon rods is 80 to 100 nm and the diameter size is uniform, and the material has ordered mesopores and larger nanopore structures inside.

[0119] Figure 2 The nitrogen adsorption-desorption isotherm (a) and the corresponding pore size distribution curve (b) of the lubrication-repair dual-function nanocomposite prepared in Example 1 are shown in FIG. Figure 2 It can be seen that the carbon nanorods have ordered mesoporous channels of 2 to 3 nm and larger nanopore structures of 22 nm. The specific surface area and pore volume of the material are 523 m 2 / g and 1.35cm 3 / g.

[0120] Figure 3 The SEM images of the lubrication-repair dual-function nanocomposite prepared in Example 1 at different magnifications are shown in FIG. Figure 3 It can be seen that after loading linseed oil and coating with paraffin, the morphology of nitrogen-doped hierarchical porous carbon nanorods did not change significantly, and still maintained a regular rod-like morphology and good dispersibility. The diameter of the carbon rods increased slightly, and the pore structure on the surface of the carbon material became less obvious due to the paraffin coating.

[0121] Figure 4 Thermogravimetric curves of nitrogen-doped hierarchical porous carbon nanorods, hierarchical porous carbon nanorods containing a repairing agent, and lubricating-repairing dual-functional nanocomposite materials prepared in Example 1 are shown in FIG. Figure 4It can be seen that after loading the repair agent, the mass loss of the nitrogen-doped multilevel porous carbon nanorods in the temperature range of 350-500°C accounts for about 49.7% of the total mass. This temperature range corresponds to the thermal decomposition range of the repair agent, indicating that after the nitrogen-doped multilevel porous carbon nanorods adsorb the repair agent, the loading amount of the repair agent is about 49.7wt%. In addition, after the nitrogen-doped multilevel porous carbon nanorods loaded with the repair agent are coated with paraffin, the mass loss of the sample in the temperature range of 350-500°C accounts for about 59.4% of the total mass. Since this temperature range is also the thermal decomposition range of paraffin, the coating amount of paraffin is about 9.7%.

[0122] Example 2

[0123] At room temperature, 0.55g hexadecyltrimethylammonium bromide (CTAB), 3.0g polyacrylic acid aqueous solution (25wt%, PAA) and 4.0g 5wt% P123 aqueous solution were dissolved in 30mL deionized water, and the mixed solution was stirred rapidly and continuously for 30min, and then 5.2g ammonia aqueous solution (28wt%) was added under stirring, and 2.08g TEOS was added. After stirring for 5min, 4.28g sucrose (C / Si molar ratio was 15) was added. The time interval between the addition of the two systems was 5min, and the stirring was continued for 30min at room temperature. After the stirring was completed, the reaction system was transferred to a reactor and placed in an oven at 80℃ for 48h. The reaction product was centrifuged and deionized and washed twice, and dried at 70℃ to constant weight to obtain a dark brown powder. The obtained dark brown powder was carbonized at 900°C for 6 h under a nitrogen atmosphere, and the silica was removed by an excess (HF to high-temperature carbonization product mass ratio of 6) 10 wt% HF aqueous solution. The powder was washed with deionized water and dried in vacuo at 70°C to constant weight to obtain nitrogen-doped hierarchical porous carbon nanorods.

[0124] 6 g of linseed oil and 24 g of anhydrous ethanol were mixed to obtain a linseed oil ethanol dispersion; 5 g of nitrogen-doped hierarchical porous carbon nanorods were subjected to vacuum treatment (4 h) to remove the gas adsorbed in the pores, and then mixed with the above linseed oil ethanol dispersion under vacuum (-0.1 MPa) and immersed for 4 h, and the above mixture was subjected to rotary evaporation for 4 h to remove the ethanol in the mixture, and the obtained oil-carrying powder was dried in a vacuum oven at 60° C. for 12 h to obtain hierarchical porous carbon nanorods containing a repairing agent (denoted as NPCS-LO, wherein the mass content of linseed oil is 55%);

[0125] 1 g of solid paraffin was dissolved in 2 g of petroleum ether to obtain a petroleum ether dispersion of paraffin, which was placed in a spray gun for later use. The above 5 g of NPCS-LO was evenly spread on a glass plate, and the NPCS-LO-1 was coated with paraffin by spraying with a spray gun. The dispersion was placed in a vacuum oven at 30°C and dried for 12 h to obtain a lubricating-repairing dual-functional nanocomposite material (denoted as NPCS-LO@WAX, wherein the mass content of paraffin was 10%).

[0126] 3g NPCS-LO@WAX and 10g epoxy resin were stirred and blended, and stirred continuously for 1h in a 45℃ water bath to obtain a suspension, which was evenly dispersed under vacuum degassing (-98kPa) and stirring. Then, 1.5g triethylenetetramine curing agent was added to the suspension and stirred for 5min. The above solution was placed in a homogenizer for degassing and poured into a polytetrafluoroethylene mold. It was first cured at room temperature for 2h, and then cured at 80℃ for 12h to obtain a self-lubricating-self-healing polymer composite material.

[0127] Figure 5 The scanning electron microscope image (a) and the surface roughness (b) of the self-lubricating and self-healing polymer composite material prepared in Example 2 show that the nitrogen-doped multi-level porous carbon nanorods are evenly dispersed in the polymer matrix as fillers, and there is no obvious agglomeration between the particles. There are no obvious cracks, pits or protrusions on the polymer surface. The surface roughness of the sample is 131.8nm, which is lower than that of pure epoxy resin.

[0128] Example 3

[0129] At room temperature, 0.55g hexadecyltrimethylammonium bromide (CTAB) and 3.0g polyacrylic acid aqueous solution (25wt%, PAA) and 4.0g 5wt% P123 aqueous solution were dissolved in 30mL deionized water, and the mixed solution was stirred rapidly and continuously for 30min, and then 5.2g ammonia aqueous solution (28wt%) was added under stirring, and 2.08g TEOS was added. After stirring for 5min, 4.28g sucrose (C / Si molar ratio was 15) was added. The time interval between the addition of the two systems was 5min, and the stirring was continued for 30min at room temperature. After the stirring was completed, the reaction system was transferred to a reactor and placed in an oven at 80℃ for 48h. The reaction product was centrifuged and washed with deionized water twice, and dried at 70℃ to constant weight to obtain a dark brown powder. The obtained dark brown powder was carbonized at 900°C for 6 h under a nitrogen atmosphere, and the silica was removed by an excess (HF to high-temperature carbonization product mass ratio of 6) 10 wt% HF aqueous solution. The powder was washed with deionized water and dried in vacuo at 70°C to constant weight to obtain nitrogen-doped hierarchical porous carbon nanorods.

[0130] 8 g of linseed oil and 32 g of anhydrous ethanol were mixed to obtain a linseed oil ethanol dispersion; 5 g of nitrogen-doped hierarchical porous carbon nanorods were subjected to vacuum treatment (4 h) to remove the gas adsorbed in the pores, and then mixed with the above linseed oil ethanol dispersion under vacuum (-0.1 MPa) and immersed for 4 h, and the above mixture was subjected to rotary evaporation for 4 h to remove the ethanol in the mixture, and the obtained oil-carrying powder was dried in a vacuum oven at 60° C. for 12 h to obtain hierarchical porous carbon nanorods containing a repairing agent (denoted as NPCS-LO, wherein the mass content of linseed oil is 62%);

[0131] 1.5 g of solid paraffin was dissolved in 2 g of petroleum ether to obtain a petroleum ether dispersion of paraffin, which was placed in a spray gun for later use. The above 5 g of NPCS-LO was evenly spread on a glass plate, and the NPCS-LO-1 was coated with paraffin by spraying with a spray gun. The dispersion was placed in a vacuum oven at 30°C and dried for 12 h to obtain a lubricating-repairing dual-functional nanocomposite material (denoted as NPCS-LO@WAX, wherein the mass content of paraffin was 15%).

[0132] 3g NPCS-LO@WAX and 10g epoxy resin were stirred and blended, and stirred continuously for 1h in a 45℃ water bath to obtain a suspension, which was evenly dispersed under vacuum degassing (-98kPa) and stirring. Then, 1.5g triethylenetetramine curing agent was added to the suspension and stirred for 5min. The above solution was placed in a homogenizer for degassing and poured into a polytetrafluoroethylene mold. It was first cured at room temperature for 2h, and then cured at 80℃ for 12h to obtain a self-lubricating-self-healing polymer composite material.

[0133] Figure 6 The SEM images of the cross-section of the self-lubricating and self-healing polymer composite material prepared in Example 3 at different magnifications show that the nitrogen-doped multilevel porous carbon nanorods are evenly dispersed in the polymer matrix, and the particles are aggregated with each other, and no obvious large cracks are observed. By increasing the addition amount of nitrogen-doped multilevel porous carbon nanorods, the internal void defects of the self-lubricating and self-healing polymer composite material are significantly reduced, which is beneficial to the improvement of the mechanical properties of the material.

[0134] Example 4

[0135] At room temperature, 0.55g hexadecyltrimethylammonium bromide (CTAB) and 3.0g polyacrylic acid aqueous solution (25wt%, PAA) and 4.0g 5wt% P123 aqueous solution were dissolved in 30mL deionized water, and the mixed solution was stirred rapidly and continuously for 30min, and then 5.2g ammonia aqueous solution (28wt%) was added under stirring, and 2.08g TEOS was added. After stirring for 5min, 4.28g sucrose (C / Si molar ratio was 15) was added. The time interval between the addition of the two systems was 5min, and the stirring was continued for 30min at room temperature. After the stirring was completed, the reaction system was transferred to a reactor and placed in an oven at 80℃ for 48h. The reaction product was centrifuged and washed with deionized water twice, and dried at 70℃ to constant weight to obtain a dark brown powder. The obtained dark brown powder was carbonized at 900°C for 6 h under a nitrogen atmosphere, and the silica was removed by an excess (HF to high-temperature carbonization product mass ratio of 6) 10 wt% HF aqueous solution. The powder was washed with deionized water and dried in vacuo at 70°C to constant weight to obtain nitrogen-doped hierarchical porous carbon nanorods.

[0136] 5 g of linseed oil and 20 g of anhydrous ethanol were mixed to obtain a linseed oil ethanol dispersion; 5 g of nitrogen-doped hierarchical porous carbon nanorods were subjected to vacuum treatment (4 h) to remove the gas adsorbed in the pores, and then mixed with the above linseed oil ethanol dispersion under vacuum (-0.1 MPa) and immersed for 4 h, and the above mixture was subjected to rotary evaporation for 4 h to remove the ethanol in the mixture, and the obtained oil-carrying powder was dried in a vacuum oven at 60° C. for 12 h to obtain hierarchical porous carbon nanorods containing a repairing agent (denoted as NPCS-LO, wherein the mass content of linseed oil is 50%);

[0137] 2 g of solid paraffin was dissolved in 4 g of petroleum ether to obtain a petroleum ether dispersion of paraffin, which was placed in a spray gun for later use. The above 5 g of NPCS-LO was evenly spread on a glass plate, and the NPCS-LO-1 was coated with paraffin by spraying with a spray gun. The dispersion was placed in a vacuum oven at 30°C and dried for 12 h to obtain a lubricating-repairing dual-functional nanocomposite material (denoted as NPCS-LO@WAX, wherein the mass content of paraffin was 17%).

[0138] 3g NPCS-LO@WAX and 10g epoxy resin were stirred and blended, and stirred continuously for 1h in a 45℃ water bath to obtain a suspension, which was evenly dispersed under vacuum degassing (-98kPa) and stirring. Then, 1.5g triethylenetetramine curing agent was added to the suspension and stirred for 5min. The above solution was placed in a homogenizer for degassing and poured into a polytetrafluoroethylene mold. It was first cured at room temperature for 2h, and then cured at 80℃ for 12h to obtain a self-lubricating-self-healing polymer composite material.

[0139] Example 5

[0140] At room temperature, 0.55g hexadecyltrimethylammonium bromide (CTAB) and 3.0g polyacrylic acid aqueous solution (25wt%, PAA) and 4.0g 5wt% P123 aqueous solution were dissolved in 30mL molecular deionized water, and the mixed solution was stirred rapidly and continuously for 30min, and then 5.2g ammonia aqueous solution (28wt%) was added under stirring, and 2.08g TEOS was added. After stirring for 5min, 4.28g sucrose (C / Si molar ratio was 15) was added. The time interval between the addition of the two systems was 5min, and the stirring was continued for 30min at room temperature. After the stirring was completed, the reaction system was transferred to a reactor and placed in an oven at 80℃ for 48h. The reaction product was centrifuged twice and washed with deionized water twice, and dried at 70℃ to constant weight to obtain a dark brown powder. The obtained dark brown powder was carbonized at 900°C for 6 h under a nitrogen atmosphere, and the silica was removed by an excess (HF to high-temperature carbonization product mass ratio of 6) 10 wt% HF aqueous solution. The powder was washed with deionized water and dried in vacuo at 70°C to constant weight to obtain nitrogen-doped hierarchical porous carbon nanorods.

[0141] 8 g of linseed oil and 32 g of anhydrous ethanol were mixed to obtain a linseed oil ethanol dispersion; 5 g of nitrogen-doped hierarchical porous carbon nanorods were subjected to vacuum treatment (4 h) to remove the gas adsorbed in the pores, and then mixed with the above linseed oil ethanol dispersion under vacuum (-0.1 MPa) and immersed for 4 h, and the above mixture was subjected to rotary evaporation for 4 h to remove the ethanol in the mixture, and the obtained oil-carrying powder was dried in a vacuum oven at 60° C. for 12 h to obtain hierarchical porous carbon nanorods containing a repairing agent (denoted as NPCS-LO, wherein the mass content of linseed oil is 62%);

[0142] 1.5 g of solid paraffin was dissolved in 2 g of petroleum ether to obtain a petroleum ether dispersion of paraffin, which was placed in a spray gun for later use. The above 5 g of NPCS-LO was evenly spread on a glass plate, and the NPCS-LO was coated with paraffin by spraying with a spray gun. The dispersion was placed in a vacuum oven at 30°C and dried for 12 h to obtain a lubricating-repairing dual-functional nanocomposite material (denoted as NPCS-LO@WAX, wherein the mass content of paraffin was 15%).

[0143] 4 g epoxy resin and 0.18 g NPCS-LO@WAX were stirred and blended, and evenly dispersed under vacuum degassing (-98 kPa) and stirring conditions. 2 g 650# polyamide resin was added and mixed evenly, and then cured at room temperature for 24 h to obtain a self-lubricating and self-healing polymer composite material.

[0144] Comparative Example 1

[0145] Under room temperature, 0.55g hexadecyltrimethylammonium bromide (CTAB) and 3.0g polyacrylic acid aqueous solution (25wt%, PAA) and 4.0g 5wt% P123 aqueous solution were dissolved in 30mL deionized water, and the mixed solution was stirred rapidly and continuously for 30min, and then 5.2g ammonia aqueous solution (28wt%) was added under stirring, and 2.08g TEOS was added. After stirring for 5min, 4.28g sucrose (C / Si molar ratio was 15) was added. The time interval between the addition of the two systems was 5min, and the stirring was continued for 30min under room temperature. After the stirring was completed, the reaction system was transferred to a reactor and placed in an oven at 80℃ for 48h. The reaction product was centrifuged and washed with deionized water twice, and dried at 70℃ to constant weight to obtain a dark brown powder. The obtained dark brown powder was carbonized at 900°C for 6 h under a nitrogen atmosphere, and the silica was removed by an excess (HF to high-temperature carbonization product mass ratio of 6) 10 wt% HF aqueous solution. The powder was washed with deionized water and dried in vacuo at 70°C to constant weight to obtain nitrogen-doped hierarchical porous carbon nanorods.

[0146] 3g of nitrogen-doped hierarchical porous carbon nanorods and 10g of epoxy resin were stirred and blended, and stirred continuously for 1h in a 45°C water bath to obtain a suspension, which was evenly dispersed under vacuum degassing (-98kPa) and stirring. Then, 1.5g of triethylenetetramine curing agent was added to the suspension and stirred for 5min. The above solution was placed in a homogenizer for degassing and poured into a polytetrafluoroethylene mold. It was first cured at room temperature for 2h, and then cured at 80°C for 12h to obtain a self-lubricating-self-healing polymer composite material.

[0147] Comparative Example 2

[0148] At room temperature, 0.55g hexadecyltrimethylammonium bromide (CTAB), 3.0g polyacrylic acid aqueous solution (25wt%, PAA) and 4.0g 5wt% P123 aqueous solution were dissolved in 30mL deionized water, and the mixed solution was stirred rapidly and continuously for 30min, and then 5.2g ammonia aqueous solution (28wt%) was added under stirring, and 2.08g TEOS was added. After stirring for 5min, 4.28g sucrose (C / Si molar ratio was 15) was added. The time interval between the addition of the two systems was 5min, and the stirring was continued for 30min at room temperature. After the stirring was completed, the reaction system was transferred to a reactor and placed in an oven at 80℃ for 48h. The reaction product was centrifuged and deionized and washed twice, and dried at 70℃ to constant weight to obtain a dark brown powder. The obtained dark brown powder was carbonized at 900°C for 6 h under a nitrogen atmosphere, and the silica was removed by an excess (HF to high-temperature carbonization product mass ratio of 6) 10 wt% HF aqueous solution. The powder was washed with deionized water and dried in vacuo at 70°C to constant weight to obtain nitrogen-doped hierarchical porous carbon nanorods.

[0149] 5 g of linseed oil and 20 g of anhydrous ethanol were mixed to obtain a linseed oil ethanol dispersion; 5 g of nitrogen-doped hierarchical porous carbon nanorods were subjected to vacuum treatment (4 h) to remove the gas adsorbed in the pores, and then mixed with the above linseed oil ethanol dispersion under vacuum (-0.1 MPa) and immersed for 4 h, and the above mixture was subjected to rotary evaporation for 4 h to remove the ethanol in the mixture, and the obtained oil-carrying powder was dried in a vacuum oven at 60° C. for 12 h to obtain hierarchical porous carbon nanorods containing a repairing agent (denoted as NPCS-LO, wherein the mass content of linseed oil is 50%);

[0150] 3g NPCS-LO and 10g epoxy resin were stirred and blended, and stirred continuously for 1h in a 45℃ water bath to obtain a suspension, which was evenly dispersed under vacuum degassing (-98kPa) and stirring. Then, 1.5g triethylenetetramine curing agent was added to the suspension and stirred for 5min. The above solution was placed in a homogenizer for degassing and poured into a polytetrafluoroethylene mold. It was first cured at room temperature for 2h, and then cured at 80℃ for 12h to obtain a self-lubricating-self-healing polymer composite material.

[0151] Test Example 1

[0152] Hardness test of self-lubricating and self-repairing polymer composites prepared in the examples and comparative examples

[0153] The hardness of the pure epoxy resin sample, the composite self-lubricating material prepared in Example 1 and Comparative Example 1 was tested by microhardness.

[0154] Figure 7 The hardness test results of the pure epoxy resin sample and the self-lubricating-self-healing polymer composites prepared in Example 1 and Comparative Example 1. As can be seen from the figure, after the nitrogen-doped multi-level porous carbon nanorod material was added to the pure epoxy resin, the hardness of the sample was improved from 22 to 46. After the lubricating-healing dual-functional nanocomposite material loaded with lubricant and repair agent was added to the epoxy, the hardness of the sample was 47, indicating that the lubricating-healing dual-functional nanocomposite material can enhance the hardness of the polymer substrate, thereby facilitating the improvement of its anti-friction and anti-wear properties.

[0155] Test Example 2

[0156] Friction test of self-lubricating and self-repairing polymer composites prepared in examples and comparative examples

[0157] The self-lubricating-self-repairing polymer composites prepared in Example 1, Examples 3-4 and Comparative Examples 1-2 and pure epoxy resin were subjected to friction tests using Test Condition 1, where Test Condition 1 was: load of 10 N, frequency of 2 Hz, diameter of the dual steel ball of 6.25 mm, friction coefficient repeated at least three times, averaged, and tested at room temperature. In addition, the self-lubricating-self-repairing polymer composites prepared in Example 2 and Example 5 were subjected to friction tests using Test Condition 2, where Test Condition 2 was: load of 5 N, sliding frequency of 1 Hz, stroke of 4 mm, time of 30 min, and test temperature of room temperature under dry friction conditions.

[0158] Figure 8 The friction coefficient variation curve of the friction test of the self-lubricating-self-repairing polymer composite material prepared for pure epoxy resin, Example 1 and Comparative Example 1 under test condition 1 is shown as a function of time. It can be seen from the figure that the average friction coefficient of pure epoxy resin is 0.79, and it remains stable during the test time. After the lubrication-repairing dual-function nanocomposite material loaded with linseed oil and paraffin was added to the pure epoxy resin, the tribological properties of the polymer were significantly improved, and the friction coefficient was reduced to 0.034, and it remained stable during the test time. It can be seen from Comparative Example 1 that after adding nitrogen-doped multi-level porous carbon nanorods to the epoxy resin, the friction coefficient of the polymer was improved, and the friction coefficient was reduced to 0.58, indicating that nitrogen-doped multi-level porous carbon nanorods have a gain effect on the tribological properties of the polymer substrate, but the effect is not as good as the lubrication-repairing dual-function nanocomposite material loaded with linseed oil and paraffin.

[0159] Fig. 9 This is a curve showing the change of friction coefficient over time for the self-lubricating and self-healing polymer composite material prepared in Example 2 under test condition 2. It can be seen from the figure that when the test conditions are changed to a loading force of 5 N, a sliding frequency of 1 Hz, a stroke of 4 mm, and a time of 30 min, the tribological properties of the polymer remain good, with a friction coefficient as low as 0.075, and remain stable during the test time.

[0160] Fig.10 The friction coefficient of the self-lubricating-self-repairing polymer composite material prepared in Example 3 and pure epoxy resin under test condition 1 varies with time. As can be seen from the figure, the average friction coefficient of pure epoxy resin is 0.68, and it remains stable during the test time. After the lubricating-repairing dual-function nanocomposite material loaded with linseed oil and paraffin is added to the pure epoxy resin, the tribological properties of the polymer are significantly improved, and the friction coefficient is reduced to 0.086, and it remains stable during the test time.

[0161] Fig.11The friction coefficient of the self-lubricating-self-repairing polymer composite material prepared in Example 4 and pure epoxy resin under test condition 1 varies with time. As can be seen from the figure, the average friction coefficient of pure epoxy resin is 0.64, and it remains stable during the test time. After the lubricating-repairing dual-function nanocomposite material loaded with linseed oil and paraffin is added to the pure epoxy resin, the tribological properties of the polymer are significantly improved, and the friction coefficient is reduced to 0.043, and it remains stable during the test time.

[0162] Fig.12 This is a curve showing the change in friction coefficient over time for the self-lubricating and self-repairing polymer composite material prepared in comparative example 2 under test condition 1. As can be seen from the figure, after the linseed oil-loaded nanocomposite material is added to the epoxy resin, the linseed oil can play a certain lubricating role during the friction test, reducing the friction coefficient in the early stage of friction. As the friction time increases, the friction coefficient gradually increases. This is because the linseed oil undergoes an oxidation reaction, which causes the lubrication performance to deteriorate.

[0163] Fig.13 This is a curve of the change in friction coefficient over time of the self-lubricating and self-repairing polymer composite material prepared in Example 5 under test condition 2. It can be seen from the figure that after changing the polymer substrate and adding the lubricating-repairing dual-functional nanocomposite material loaded with linseed oil and paraffin to the polymer, the tribological properties of the polymer can still be significantly improved, and the friction coefficient is reduced to 0.073, and remains stable during the test time.

[0164] Test Example 3

[0165] Self-repairing performance test of self-lubricating-self-repairing polymer composites prepared in examples and comparative examples

[0166] The self-lubricating and self-repairing polymer composites prepared in Examples 1 to 4 were tested for self-repairing performance. The test method was as follows: a 4 mm long wear mark was obtained by reciprocating friction on the sample surface with a loading force of 10 N using a multifunctional friction and wear tester (RTEC-5000). The scratched composite material was placed at 60°C for 2 hours, and the changes in the morphology and volume of the scratched composite material were observed.

[0167] Fig.14The ultra-depth microscope images of the wear marks of the self-lubricating-self-repairing polymer composite material and pure epoxy resin prepared in Example 4 after the friction test, wherein (a) is the ultra-depth microscope image of the wear marks of pure epoxy resin after the friction test, (b) is the ultra-depth microscope image of the wear marks of pure epoxy resin after the self-repairing process, (c) is the ultra-depth microscope image of the wear marks of the self-lubricating-self-repairing polymer composite material prepared in Example 4 after the friction test, and (d) is the ultra-depth microscope image of the self-lubricating-self-repairing polymer composite material prepared in Example 4 after the self-repairing process. It can be seen from the figure that after the tribological performance test, the surface of the self-lubricating-self-repairing polymer composite material sample has a relatively obvious wear mark, and after repair, the wear mark becomes significantly lighter. However, there is no obvious change in pure epoxy resin, indicating that the lubrication-repairing dual-function nanocomposite plays a key role in the repair performance of epoxy resin materials and can effectively improve its self-repairing ability.

[0168] Fig.15 The depth change curve of the wear scar before and after repair of the self-lubricating-self-repairing polymer composite material and pure epoxy resin prepared in Example 4. As can be seen from the figure, after adding the lubricating-repairing dual-function nanocomposite material to the epoxy resin, the repair performance of the polymer material is significantly enhanced, and the wear scar depth is reduced from 35μm to 0.03μm. However, there is no obvious change in pure epoxy resin.

[0169] In summary, the present invention first uses a vacuum impregnation method to load linseed oil on the multi-level porous carbon nanorods, and uses the oxidation of linseed oil to form a self-healing film to play a self-repairing role; the paraffin dispersion solution is sprayed on the multi-level porous carbon nanorods after the oil is loaded. The paraffin can not only be used as a part of the wall material to encapsulate the pore structure of the multi-level porous carbon nanorods, but also can be used as a good lubricant to improve the tribological properties of the composite material. The present invention combines the multi-level porous carbon nanorods with linseed oil and solid paraffin and adds them to the epoxy resin. The rich nanopore structure in the carbon nanorods provides sufficient storage space for the repair agent, which can act as a buffer pool for the repair agent under instantaneous high temperature and high pressure to achieve continuous sustained release of the repair agent, and the mesopore and micropore structure can store a large amount of repair agent, and the interconnected pore structure is conducive to the efficient transmission and diffusion of the repair agent, and quickly forms a high-quality repair film on the surface of the friction pair. Under the action of friction heat, the coated paraffin lubricant will be converted from solid to liquid, forming a lubricating oil film on the surface of the friction pair. Under the synergistic effect of solid paraffin and vegetable oil, the purpose of improving the wear-resistant and anti-friction properties of the composite material and repairing the damaged composite material is achieved, the maintenance cost is reduced, the composite material can be repeatedly used, and the service life of the composite material is extended.

[0170] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A lubrication-repair dual-function nanocomposite material, comprising nitrogen-doped multi-level porous carbon nanorods, a repair agent located in the pores of the nitrogen-doped multi-level porous carbon nanorods, and a lubricant coated on the surface of the nitrogen-doped multi-level porous carbon nanorods.

2. The lubrication-repair dual-function nanocomposite material according to claim 1, characterized in that: The nitrogen-doped multi-level porous carbon nanorod has nanopores and mesopores, the pore size of the mesopores is 2 to 10 nm, and the pore size of the nanopores is 20 to 30 nm; the length of the nitrogen-doped multi-level porous carbon nanorod is 0.03 to 10 μm; The mass content of the repair agent in the lubricating-repairing dual-function nanocomposite material is 20-62%, and the mass content of the lubricant is 5-20%; The repair agent includes one or more of drying oil, isocyanate and epoxy resin; The lubricant includes a solid lubricant.

3. The method for preparing the lubricating-repairing dual-functional nanocomposite material according to claim 1 or 2, comprising the following steps: The nitrogen-doped hierarchical porous carbon nanorods are mixed with a repairing agent and subjected to vacuum impregnation treatment to obtain hierarchical porous carbon nanorods containing the repairing agent; The multi-level porous carbon nanorods containing the repairing agent are coated with a lubricant dispersion to obtain a lubricating-repairing dual-function nanocomposite material.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the nitrogen-doped hierarchical porous carbon nanorods to the repair agent is 5-10:1-5; The nitrogen-doped hierarchical porous carbon nanorods are first subjected to vacuum treatment before use; The vacuum degree of the vacuum impregnation treatment is -0.08 to -0.1 MPa, and the time is 2 to 4 hours.

5. The preparation method according to claim 3, characterized in that: The lubricant dispersion is obtained by dispersing the lubricant in an organic solvent; the organic solvent includes one or more of ethanol, petroleum ether, isopropanol, carbon disulfide, xylene, ether, benzene, chloroform and carbon tetrachloride; the mass ratio of the lubricant to the organic solvent is 1:5-10; The mass ratio of the lubricant to the multi-level porous carbon nanorods containing the repairing agent in the lubricant dispersion is 1:2-5.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The method for preparing the nitrogen-doped multi-level porous carbon nanorods comprises the following steps: (1) self-assembling an ionic surfactant, a water-soluble polymer with opposite charges, and a non-ionic block copolymer under alkaline conditions to obtain a hierarchical pore structure template; (2) Adding a silicon source and a carbon source into the hierarchical porous structure template, sequentially performing a hydrolysis and polycondensation reaction of the silicon source, deposition of the carbon source, carbonization and removal of silicon dioxide, to obtain doped hierarchical porous carbon nanorods.

7. The preparation method according to claim 6, characterized in that: In step (1), the ionic surfactant comprises a long-chain alkyl quaternary ammonium salt or a Gemini quaternary ammonium salt surfactant; The water-soluble high molecular polymer with opposite charges includes polyacrylic acid; The nonionic block copolymer includes P123, L31 or L35; The mass ratio of the ionic surfactant to the water-soluble high molecular polymer with opposite charges is 1:7-15; The mass ratio of the ionic surfactant to the nonionic block copolymer is 1:4-16; The self-assembly time is 30 to 60 minutes; the alkaline condition pH value is 8 to 10; In step (2), the molar ratio of silicon in the silicon source to carbon in the carbon source is 1:5 to 20; The temperature of the silicon source hydrolysis and polycondensation reaction is 25 to 80° C. and the time is 24 to 48 hours; The temperature of the carbon source deposition is 25 to 80° C., and the time is 12 to 24 hours; The carbonization includes pre-carbonization and high-temperature carbonization. The temperature of the pre-carbonization is 80-120° C. and the time is 24-48 hours; the temperature of the high-temperature carbonization is 800-900° C. and the time is 4-6 hours.

8. Use of the lubricating-repairing dual-function nanocomposite material according to any one of claims 1 to 2 or the lubricating-repairing dual-function nanocomposite material prepared by the preparation method according to any one of claims 3 to 7 as a filler.

9. A self-lubricating-self-repairing polymer composite material comprising a polymer and a filler, wherein the filler comprises the lubricating-repairing dual-functional nanocomposite material according to any one of claims 1 to 2 or the lubricating-repairing dual-functional nanocomposite material prepared by the preparation method according to any one of claims 3 to 7.

10. Application of the self-lubricating and self-repairing polymer composite material according to claim 9 in mechanical parts in the fields of petrochemical industry, aerospace, automobile industry or marine heavy industry.